Hormonally Induced Changes in the Stem and Petiole Anatomy and Cellulase Enzyme Patterns in Phaseolus vulgaris L. - Linkins, Arthur E. (1973)
Time course changes were observed in petiole and stem anatomy and cellulase enzyme patterns in bean (Phaseolus vulgaris L.) explants when 10(−5) or 10(−2)m indoleacetic acid in lanolin paste was applied to acropetal cut surfaces in the presence or absence of ethylene. Auxin (10(−2)m) in the presence of ethylene stimulated rapid ordered cell division and dedifferentiation, with ensuing lateral root formation. Auxin (10(−5)m) caused moderate cortical swelling, pit formation in pith parenchyma, and chloroplast development in certain cortical cells. Exogenous ethylene reduced cell division activity and caused cortical cell swelling and separation. Removal of endogenously generated ethylene by mercuric perchlorate resulted in less ordered cell division patterns and no lateral root formation. Auxin treatments enhanced formation of an active acidic pI cellulase, exogenous ethylene-stimulated formation of an active basic pI cellulase. The absence of basic pI cellulase activity by the removal of endogenously generated ethylene suggests a close dependence of basic pI cellulase activity on ethylene.